Can publicly reported data be used to understand performance in an Australian rural hospital?. Issue 1 (January 2021) - Lloyd, Sheree; Cliff, Cynthia; FitzGerald, Gerard; Collie, Jean
Background: Despite agreement among policymakers, funders, consumers and researchers about the value of public reporting of health information, limited attention has been paid to how it can be used to understand the performance of rural hospitals. Objective: To determine whether publicly available information can be used to measure health service performance in a rural hospital. Method: The study used performance data routinely reported for public consumption in Australia. Data across four domains, multiple measures and time periods were collected to examine access and equity; efficiency and sustainability; quality, safety and patient orientation; and employee engagement. Performance of the rural hospital was examined using a visualisation tool. Results: Visualisation of multiple measures of performance over time was achievable but required a high degree of health information management skills. Conclusion and implications: Publicly reported data can be used to represent performance for a rural hospital. Timeliness, level of detail available and peer groupings of data limits optimal utility. Consumers, clinicians and health service managers wanting to understand the performance of rural hospitals will need to use significant health information management skills to gain a picture of performance. Further research in the applied use of publicly available performance data and relevant dashboards for rural hospitals is suggested.